Virtual teams and knowledge sharing via digital platforms: Evidence from an inter-organizational network context - Ben Arfi, Wissal; Sahut, Jean-Michel; Hikkerova, Lubica; Braune, Eric (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
In the context of open innovation, we study the conversion of groups' tacit knowledge, in order to achieve effective virtuality between members of cross-firm teams and optimize innovative projects through three cases of international platforms. The results show that virtual teams succeed in sharing knowledge through digital platforms thanks to communication, integration, an innovative corporate culture at the micro level, a participative approach, transformative leadership and transparency at the meso level, as well as participative governance, long-term commitment and a shared common strategy at the macro level.